Przełom i nowe otwarcie. Relacje polsko-niemieckie na przełomie lat 80. i 90. XX wieku - Ruchniewicz, Krzysztof (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The 30th anniversary of signing the Treaty of Good Neighbourship and Friendly Cooperation is a natural impulse for recounting the most important events preceding this act. It crowned with success the process of Polish–German rapprochement initiated in November 1989. The treaty outlined the framework of future Polish–German relations on various planes
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne